Implementasi Internet of Things Untuk Parkir Mobil Dengan Pembayaran Menggunakan QR Code - Jemima Ciani Setiawan; Resmana Lim; Justinus Andjarwirawan (Jurnal Infra, 2020)
Along with the increasing number of 4-wheeled vehicles (cars), problems related to the availability of parking spaces for cars have also increased. Flow in and out of the car that is not balanced with the capacity of the parking lot. This is because the drivers/visitors do not have information about the availability of parking space before being in the parking lot.In this study, a trial will be conducted to help resolve the problem by implementing internet of things technology at the entrance and exit gates of the parking lot, and detecting the availability of parking slots. Then use a digital payment system with QR Code media for parking payments. Implementation of Internet of Things that is used at the entrance and exit gates is to use infrared sensors to detect the presence of cars at the gate and servo motor to control the parking entrance gate. While Internet of Things technology to detect parking slots is to use ultrasonic sensors. The ultrasonic sensor will always detect and send the status of each slot on the server. Then for the payment system created, will use the QR Code media as proof of parking transactions. The entire technology and system will be integrated in an application, so that it is expected to help the problem of the availability of parking lots and simplify the parking payment process.